Efficacy and side effects of radiation therapy in comparison with radiation therapy and temozolomide in the treatment of measurable canine malignant melanoma. (10th November 2014) - Cancedda, S.; Rohrer Bley, C.; Aresu, L.; Dacasto, M.; Leone, V. F.; Pizzoni, S.; Gracis, M.; Marconato, L.
Abstract: Prognosis for unresectable canine malignant melanoma (MM) is typically poor, and therapeutic approaches remain largely palliative. A bi‐institutional trial was conducted to compare efficacy and safety of radiation therapy (RT) and RT with post‐radiation temozolomide in dogs with chemotherapy‐naïve, measurable MM. RT consisted of 5 × 6 Gy fractions over 2.5 weeks. Dogs whose owners wished to pursue chemotherapy received adjuvant oral temozolomide (60 mg m −2 for 5 days every 28 days). Fifteen dogs were treated with RT only (Group 1) and 12 dogs subsequently received temozolomide (Group 2). Overall response rate was similar between Group 1 (86.7%) and Group 2 (81.1%). Median time to progression (TTP) was significantly longer in Group 2 (205 days) compared to Group 1 (110 days; p = 0.046). Survival time was not significantly different between groups. Both treatments were well tolerated. Post‐radiation temozolomide has a good safety profile, and may improve TTP in MM when compared to coarse fractionated RT.